XV. Országos Kisplasztikai Biennálé Pécs, 1997. - Hungarian Small Sculpture Biennale Pécs 1997; Sarkany, Jozsef; Janus Pannonius Múzeum, Pécs ([S.l.] : [s.n.], 1997)
Laszlo, Babos ; Ildikó, Bakos ; Zoltán, Balanyi ; Eszter, Balás ; Márton, Barabás ; Tamás, Baráz, József, Benedek ; Laszlo, Békési ; Vendel, Bicsár ; Zoltán, Bohus ; et al.
15th Hungarian Small Sculpture Biennale, starting from April 1997, Janus Pannonius Múzeum, Pécs
kunstcatalogus